The History and future of the World Trade Organization - VanGrasstek, Craig (WTO GenevaCH, 2013)
Presents an analysis of the WTO. Focuses on change over time and examines developments by subject; information is presented with a view towards either comparing the WTO with the GATT period or in illuminating the changes that have taken place over the WTO's own tenure.